2015
DOI: 10.1007/s00276-015-1486-8
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the quadriceps tendon: an anatomic and morphometric study to guide tendon harvesting

Abstract: The present anatomical study confirmed that QT should be harvested from the central and centromedial regions. Mean thickness was 7.84 mm at the patellar insertion, 7.37 mm at 20 mm from the insertion, 6.41 at 40 mm, 5.61 at 60 mm and 4.33 at 100 mm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 10 publications
2
20
0
Order By: Relevance
“…Studies have shown a similar decrease in anterior QT width working proximally 18,33 and narrowing, followed by widening, when examining the width of the posterior aspect of the QT. 22 One study even described a phenomenon similar to the “splay” described here: an “additional thickness corresponding to tendinous expansion” on the posterior aspect of the QT. 22 Although QT thickness was not a focus of this study, our data do show a decreasing depth, or thickness, working proximally from the patella (unpublished data), similar to adult studies.…”
Section: Discussionmentioning
confidence: 72%
“…Studies have shown a similar decrease in anterior QT width working proximally 18,33 and narrowing, followed by widening, when examining the width of the posterior aspect of the QT. 22 One study even described a phenomenon similar to the “splay” described here: an “additional thickness corresponding to tendinous expansion” on the posterior aspect of the QT. 22 Although QT thickness was not a focus of this study, our data do show a decreasing depth, or thickness, working proximally from the patella (unpublished data), similar to adult studies.…”
Section: Discussionmentioning
confidence: 72%
“…Still, the QT is the least used graft for primary ACL reconstruction, with about 10% of the reconstructions being performed with a quadriceps graft 27, 29. It is expected that the use of this graft will be increasing in the future 30 as data shows good anatomical and biomechanical characteristics to the QT graft 26, 31, 32. Also, studies have shown good clinical results with QT graft compared to patellar tendon graft, still considered gold standard by some authors.…”
Section: Discussionmentioning
confidence: 99%
“…8 Quadriceps tendon thickness also showed significant correlation with patellar height. 9 This study aimed at the morphometric and comparative analysis of patella in eastern part of India.…”
Section: Introductionmentioning
confidence: 99%